Non-cardiac surgery and anaesthesia in children with congenital heart disease (1996)
Children with Congenital Heart Disease (CHD) presenting for non-cardiac surgery have various physiological and functional abnormalities and thus pose great challenges to the anaesthetist. This one year prospective study was undertaken to determine the incidence of CHD in children presenting for noncardiac surgery, the type of lesions and anaesthetic course. Five patients (1.5%) out of a total of 324 children aged from birth to twelve years who had surgery during the study period were found to have CHD, ventricular septal defect (VSD) being the commonest cardiac lesion. Surgery was for cataract extraction and herniorrhaphy. Although all the children had been previously treated or were on current treatment for additional medical problems, surgery under closely monitored balanced general anaesthetic technique was found to be safe.